Pengalaman Keluarga dalam Merawat Anggota Keluarga dengan gangguan Jiwa - Prastiwi, Eki (Journal of Health Education and Literacy, 2025)
People with mental disorders (ODGJ) have mental, cognitive, and behavioral abnormalities that make it difficult for someone to adapt to their environment, others, society, or themselves. West Sulawesi is an area with a high number of people with mental disorders (ODGJ) spread across six districts, making it necessary to study the experiences of families caring for ODGJ family members in Polewali Mandar. This research is qualitative with a phenomenological approach. The study population consisted of 57 people, with a sample size of 7. The data collection method is multi-source evidence, with data collected through interviews, measurements, and document studies. Based on the findings, the researcher successfully identified 5 questions, with the first theme being the obstacles experienced. It is true that all families experience obstacles in parenting and costs. The second theme is the family's sense of security and comfort, where the family still feels safe and comfortable because they are accustomed to caring, but in some cases, patients who are prone to outbursts can trigger discomfort. The third theme is the issue of cost. In the treatment process, informants generally did not feel burdened because they used BPJS (National Health Insurance), but expenses in other areas could be extra, such as transportation and daily needs. The fourth theme is limitations in performing daily activities, where participants 1, 2, 4, and 5 were still able to be active, while participants 3, 6, and 7 felt disrupted. The fifth theme is support from the surrounding community. Overall, informants stated that the entire community provided emotional and informational support related to treatment.